Pengaruh Pendidikan Ekonomi Informal dan Literasi Keuangan Terhadap Pengelolaan Keuangan Mahasiswa - Imania, Inten Noor; Ahman, Eeng; Disman, Disman (Neolectura, 2024)
This study aims to examine the effect of informal economic education and financial literacy on financial management in college students. The research method used is quantitative method. The subject of this research is the accounting study program at the University of Garut Class of 2020/2021 with a total of 90 students. The sampling method in this study was the saturated sampling method. The data collection technique was carried out through a questionnaire. The data analysis used is multiple linear regression. The results showed that informal economic education and financial literacy have a positive and significant influence on financial management in students. This shows that the higher the informal economic education and financial literacy of students, the higher the financial management of these students.